Bronchial arterial embolisation for massive haemoptysis in cavitary sarcoidosis - Loh, Geoffrey Andrew (BMJ Publishing Group, 2013)
A 48-year-old non-smoking man with a 6-year history of pulmonary cavitary sarcoidosis presented with acute onset of haemoptysis of approximately 600 ml. Prior episodes of haemoptysis had resolved only after serial upper lobe wedge resections bilaterally and steroids. A chest CT identified bilateral upper lobe cavitary lesions with extravasation of contrast from a large right upper lobe cavity. The patient underwent urgent bronchial angiography and subsequent bronchial artery embolisation of a left bronchial artery and three right bronchial arteries. He was started on methotrexate and steroids for refractory sarcoidosis. Two years after embolisation, the patient remained haemoptysis-free with his sarcoid well controlled on methotrexate monotherapy.